MeSsy identities: an ethnographic exploration of a multiple sclerosis support group - Alyse Keller Johnson (Qualitative Research in Medicine & Healthcare, 2024)
The following is an ethnographic study of a multiple sclerosis (MS) support group. This study underscores the importance of access to counternarratives for individuals with chronic illness and disabilities through organizational structures such as support groups. This work can help those with disabilities/chronic diseases, such as MS, because it provides a space for discussing the communicative forces that shape individual experiences of living with disability and chronic illness. Thus, this study seeks to understand how pharmaceutical representatives’ and doctors’ grand medical narratives influence the communication of MS support group attendees and their construction/ performance of self. This study shows that participation in support groups provides a space to renegotiate identity in which new forms of self can develop external to the dominant discourse. The support group becomes a space where counternarratives of empowerment develop in the face of master narratives.